Simulasi Komparatif: Empat Algoritma Penjadwalan CPU dengan Pemodelan Interupsi I/O Menggunakan OS-SIM - Mufid Athooyaa; Mirza Putra Firmansyah Firmansyah; Djuniadi Djuniadi; Alfian Ardhiansyah (ELECTRON Jurnal Ilmiah Teknik Elektro, 2026)
CPU scheduling is a fundamental component in operating systems that determines processor utilization efficiency and system responsiveness. The objective of this research is to comparatively evaluate four classic CPU scheduling algorithms, namely First Come First Served (FCFS) multiprogramming, Preemptive Shortest Job First (SRTF), Preemptive Priority, and Median Round Robin, considering the effects of I/O interruption. The research method employs experimental simulation through OS-SIM with 12 test sample processes covering CPU bound and I/O bound characteristics. Performance evaluation is conducted based on Average Waiting Time (AWT), Average Turnaround Time (ATT), Average Response Time (ART), CPU efficiency, and throughput parameters. Simulation results demonstrate that the Preemptive SJF (SRTF) algorithm produces the most efficient performance with AWT of 15.5 s and ATT of 20.5 s, lower than other algorithms. FCFS and Median Round Robin excel in providing quick initial response with ART of 10.58 s and 10.42 s respectively, but result in higher waiting times. Preemptive Priority stands in the middle position with AWT of 18 s and ATT of 23 s, but potentially causes starvation for low-priority processes. The novelty of this study lies in the explicit modeling of I/O interruption within a multiprogramming environment, an aspect that has not been systematically addressed in previous comparative studies. This research contributes a guideline for selecting optimal CPU scheduling algorithms based on system workload characteristics, recommending SRTF for batch processing scenarios, while FCFS and MRR are more suitable for interactive environments that prioritize responsiveness